The Influence of the Suzuki Method on Violin Teachers’ Emotion Wellness in Malaysia - Young, Joey; Sinn, Ow Su; Jie, Lee Ying (Universitas Negeri Semarang, 2025)
Despite growing enthusiasm for music examinations, the music education landscape in Malaysia has led to dissatisfaction among music teachers due to limited developmental growth in violin pedagogy. Based on the available literature, a research gap is observed in violin pedagogy and the emotional wellness of music teachers in Malaysia. This qualitative, exploratory, ethnographic research investigates the influence of the Suzuki Violin Method, recognized for its holistic benefits globally, on the emotional well-being of violin teachers in urban areas of Malaysia. Semi-structured interviews with six Suzuki-trained violin teachers are analyzed thematically to examine the effects of the Suzuki method on teachers’ self-identity, focusing on self-efficacy, commitment, agency, and musician-teacher comprehension. Using symbolic interactionism and Wagoner’s framework of music teacher identity, the findings reveal that the Suzuki method fosters a positive teaching identity, contributing to meaningful interactions and positive experiences that result in the teachers’ positive emotional wellness. The study highlights the potential of Suzuki philosophy to enhance both teaching practices and teacher well-being, encouraging the need for wider adoption and promoting awareness of self-reflection and emotional well-being among the teachers involved. Furthermore, this study provides insight into the challenges unique to this demographic, contributing to the development and regeneration of Malaysia’s music education.